Decision-making process of the development components of an institution of higher learning - Santos, Daniel S.
The study looked into the decision-making process of the development components of Philippine Wesleyan College, a medium-sized church-related institution of higher learning in Cabanatuan City, in terms of curriculum, faculty, student affairs, buildings and facilities, research and community outreach. The decision-making process model of J. Victor Baldridge is adapted in the findings of the study.